Inductively coupled power transfer (ICPT) for electric vehicle charging - A review - Kalwar, Kafeel Ahmed; Aamir, Muhammad; Mekhilef, Saad (Elsevier, 2015)
The deficiency in the availability of petroleum products has given rise to the incorporation of electric vehicles (EVs) globally as a substitute for the conventional transportation system. Significant research has been pursued over last two decades in the development of efficient EV charging methods. A preliminary review of few methods developed for wireless charging revealed that ICPT is a promising and convenient method for the wireless charging of EVs. This paper includes the equivalent circuit analysis and characteristics of the ICPT system and focuses on the research progress in respect of the designs for the charging coil, leakage inductance compensation topologies, power level enhancement and misalignment toleration. The improvement in these factors has been essential for the implementation of EV charging. A brief discussion over design process and control of ICPT system has been added. Conclusions have been made on the basis of the information extracted from the literature and some future recommendations are provided. (C) 2015 Elsevier Ltd. All rights reserved.